“Paperwork is so important!” : processes of literacising in bureaucratic contexts in Benin and Bolivia - Abou Moumouni, Issifou; Krauß, Rebekka (cultura & psyché, 2023)
In both Bolivia and Benin, the state presumes that citizens can navigate its bureaucracy even if it does not provide them with the requisite literacy skills. However, bureaucratic procedures are highly characterised by literacy and digital literacy and people with little or no literacy require alternative strategies to manage them. This article contributes to debates on (il)literacy and bureaucracy studies by looking at the learning practices of persons with little or no literacy competence in La Paz and El Alto, Bolivia, and Parakou, Benin. It investigates their ways of coping with such bureaucratic requirements and especially how they manage to acquire specific literacy abilities in order to complete procedures. Our conclusions are based on empirical data obtained through various kinds of interviews and participant observation that we carried out during more than 12 months of fieldwork.
Keywords: (Un)learning; Literacy; Illiteracy; Digital literacy; Administrative procedures